Symbolic Function and Meaning of Ontalan Tradition in Maduranese Wedding - Hasan, Nor; Susanto, Edi (el Harakah: Jurnal Budaya Islam, 2019)
Ontalan is a Maduranese tradition at weddings. The term of ontalan (oncal: Javanese) means throwing, which is throwing money at the bride and groom when they are sitting side by side. As a tradition, ontalan is something that has been done and has become part of the life and local wisdom of the Pamekasan community which is still being implemented. The social function of ontalan is to strengthen social relations between families, a symbol of family cohesiveness, and also as a symbol of agreement on the marriage of the bride and groom. While the economic function of ontalan is in order to help families who have an intention and as a provision of life for a new couple. Some people continue to try preserving these traditions through inheritance to the next generation, construction and modification so that the tradition is in accordance with the times. Ontalan adalah tradisi orang Madura di pesta pernikahan. Istilah ontalan (oncal: Jawa) berarti melempar, yaitu melempar uang ke pengantin saat mereka duduk berdampingan. Sebagai sebuah tradisi, ontalan adalah sesuatu yang telah dilakukan dan telah menjadi bagian dari kehidupan dan kearifan lokal masyarakat Pamekasan yang masih dilaksanakan. Fungsi sosial ontalan adalah untuk memperkuat hubungan sosial antar keluarga, simbol kekompakan keluarga, dan juga sebagai simbol kesepakatan tentang pernikahan mempelai pria dan wanita. Sedangkan fungsi ekonomi ontalan adalah untuk membantu keluarga yang memiliki niat dan sebagai bekal hidup bagi pasangan baru. Beberapa orang terus mencoba melestarikan tradisi ini melalui warisan kepada generasi berikutnya, konstruksi dan modifikasi sehingga tradisi tersebut sesuai dengan zaman.